The UN Working Group on Arbitrary Detention : commentary and guide to practice / Jared Genser. - Genser, Jared (Cambridge University Press, 2020)
The United Nations Working Group on Arbitrary Detention is the first comprehensive review of the contributions of this important institution to understanding arbitrary detention today. The Working Group is a body of five independent human rights experts that considers individual complaints of arbitrary detention, adopting legal opinions as to whether a detention is compatible with states' obligations under international law. Since its establishment in 1991, it has adopted more than 1,200 case opinions and conducted more than fifty country missions. But much more than a jurisprudential review, these cases are presented in the book in the style of a treatise, where the widest array of issues on arbitrary detention are placed in the context of the requirements of multilateral treaties and other relevant international standards. Written for both practitioners and serious scholars alike, this book includes five case studies and a foreword by Archbishop Desmond M. Tutu.